Prompting with Wearable Technology to Increase Teaching Behaviors of a Preservice Special Education Teacher - Markelz, Andrew M.; Taylor, Jonte C.; Scheeler, Mary Catherine; Riccomini, Paul J.; McNaughton, David B. (Journal of the American Academy of Special Education Professionals, 2018)
Classroom management is essential for student related academic and behavioral outcomes. Novice teachers, as well as faculty members, of special education teacher preparation programs report insufficient preparedness in providing meaningful behavioral supports to exceptional learners. With advancements in technology, tactile prompting is a promising modality for teachers to overcome cognitive overload and facilitate more effective practice of classroom management behaviors. We used a multiple-baseline, across behaviors design to assess the effects of prompting with wearable technology (i.e., Apple Watch™) to increase behavior-specific praise, active questioning, and classroom scanning of a preservice special education teacher. Results indicate a functional relation between prompting with wearable technology and targeted increases across multiple behaviors. Behavior-specific praise rates, however, faded synchronously with prompting fades. The participant rated the intervention as a non-intrusive, effective device to increase teaching behaviors. Implications for future research and classroom use are discussed.